أثر استراتيجية الاستقطاب في تحقيق التنمية السياحية المستدامة (( دراسة تطبيقية في عينة من فنادق الدرجة الممتازة)) (المجلة العراقية للعلوم الاقتصادية, 2018)
Two Variables interacted to form the intellectual and philosophical framework of this study, which is represented by "Recruitment Strategy, Sustainable tourism development". The planning of active Recruitment Strategy for the human resources will lead essentially and effectively to point out the right thoughts of the managers and the hotel institutions towards their activities, and affect the existence and continuity of these establishments focusing on their past experience to face the future through their attempt to achieve distinction . The study started with exploring the problem which is expressed through a number of theoretical and applied questions. The response to these questions is meant to explain the theoretical philosophy and the notional concepts of these variables as they are new subjects in Arab environment, in general, and in Iraqi environment, in particular. Then, there is testing the co-relationships and the impact relationships and the possibility of achieving them in the area of application which is constituted of the five-star hotels in Iraq. The sample of the study consists of (89) managers. The importance of the study involves in establishing a philosophical and notional evolvement for the nature of the variables of the study depending on the efforts of applying the study on the actual nature of the recruitment strategy for achieving the Sustainable tourism development. In order to achieve this, nine main hypotheses are formed, all are tested and accepted by a set of non-instructed statistical tools, and questionnaire is used as a way to collect the data and information from the sample of the study, The study also presented a set of recommendations the most important of which is the concern with putting a strategic work program depending on establishing continual and strong relations with the working personnel which leads to the contribution in recruiting of what the hotel needs of the qualified people, their number and their qualifications .